AN EVALUATION OF SERIOUS GAMES AND COMPUTER-BASED LEARNING ON STUDENT OUTCOMES IN UNIVERSITY LEVEL GEOGRAPHIC EDUCATION - ERVIN, Daniel; LOPEZ-CARR, David (European Journal of Geography, 2022)
We examine the effects of completing ‘serious game’ and computer-based learning assignments upon learning outcomes for undergraduate university students in an introductory human geography class (n = 177). The students completed one of the two experimental assignments as well as a control assignment that did not involve gaming, gathering data, or a computer. The groups were contrasted on their own evaluation of the assignments as well as their performance in multiple class outcomes. Our analysis found few significant differences between the group’s selfevaluations of the assignments, their performance on the assignments, or their overall class grade. However, the ‘control group’ of students, who completed the control versions of the activities, performed significantly (p> .05) better on topic-relevant questions on the midterm (86% correct vs. 75%) and final examinations (94% vs. 87%). We conclude that completing the pen and paper version of the assignments resulted in better understanding of subject material.